X-ray imaging at synchrotron research facilities. (January 2021) - Ponchut, Cyril; Tartoni, Nicola; Pennicard, David
Abstract: At synchrotron facilities, many X-ray imaging and diffraction experiments require pixel detectors with minimal noise, high speed and reasonably small pixel size, all of which can be achieved with the Medipix ASIC family. So, ESRF, Diamond Light Source and DESY have developed detector systems based on Medipix. In this paper, we report on these developments, with an emphasis on the challenges involved building readout systems and the potential of the Medipix family ASICs in this field of research. Highlights: ESRF, Diamond Light Source, DESY synchrotrons develop Medipix-based X-ray detectors. Maxipix, Merlin, Lancelot, Excalibur, Lambda are Medipix synchrotron detectors. Photon-counting Medipix detectors provide noiseless data and high frame rates. Medipix applications at synchrotrons include coherent diffraction, scattering, imaging. Medipix with high-Z semiconductor pixel sensors enable high-energy X-ray imaging.